Investigation of ultrasonification effect on physical and electrical characteristics of Bax Sr1-x TiO3 thin films prepared using Sol-Gel method - Ruhaizi Mohd Hatta (School of Microelectronic Engineering, 2012)
The main objective of this project is to improve the current BST thin film in terms of surface and electrical properties through the sol-gel method.